Rationalist Hymnbooks in the Early 19th century Latvian Literature: an Episode in the History of Reading in Livonia and Courland - Daija, Pauls (Knygotyra, 2018)
[full article, abstract in English; abstract in Lithuanian]The article explores the introduction of the Rationalist hymnbooks in the Latvian literature during the first decade of the 19th century as an episode in the history of reading in Livonia and Courland. The reformed hymnbooks met with strong resistance of the Latvian reading public that might be explained by the significant place of the traditional hymnbook in peasants’ lives. In the article, the process of the introduction of new hymnbooks has been analysed along with the reasons for a dismissive attitude from the Latvian readers. In the context of the history of reading, the introduction of new hymnbooks has been described in terms of segregation in the reading public, as analysed by the Latvian scholar Aleksejs Apīnis.
Keywords: Theological Rationalism, Lutheran hymnbooks, history of reading, Popular Enlightenment, history of Latvian literature